Efeito da cooperação na associação entre ativos intangíveis e a vantagem competitiva - Damke, Fernando (2022)
This study aimed to verify the effect of cooperation on the association between intangible assets and competitive advantage in a franchising environment. In order to achieve the proposed objective, the dimensions of the intangible asset, human, structural and relational capital were approached, adding the psychological intangible dimension. Having represented the internal dimensions, to add robustness to the external dimension, the cooperation network was added in order to verify the interactions of these dimensions with the competitive advantage. A single case study was carried out with a quantitative approach in a company that operates in the area of information technology. Data collection was performed using a questionnaire and the data were analyzed using descriptive statistics and structural equation modeling (Partial Least Square - PLS). The research results consisted of a structural model with explanatory power of the dependent variable organizational performance of 70.6%. It was found from the descriptive statistics points of improvement needed to optimize processes and thus be able to generate competitive advantage. It appears that with the addition of psychological capital and the dimensions of cooperation networks, it is possible to observe the creation of competitive advantage for companies. Based on these results, it is concluded that the company is relevant to carry out the holistic management of the intangible asset and the cooperation network, since these are key elements in generating competitive advantage. However, the limitations of the scope of the research instigate future research in other companies in the same or different sectors in order to broaden the discussions of the results